A study of the effect of iron (III) compoundson oxidation of iron (II) ions by atmospheric oxygen - Яворський, Віктор Теофілович; Калимон, Ярослав Андрійович; Рубай, Ольга Іванівна (Eastern-European Journal of Enterprise Technologies, 2015)
Deferrisation of groundwater has been performed by many methods whose choice depends on the form in which iron (Fe) compounds exist in water and on its chemical composition. A number of published studies have proved that the iron (III) compounds’sediment used in the filtering substrate has a catalytic effect on the oxidation process. The same property of iron (III) compounds’sedimentis observed in the sediment layerresulting from contact purification of water. However, in the case of filtering, due to the large-size granules of the filter substrate, the specific surface area of the autocatalytic layer is small, which significantly reduces the system performance. In the schemes of contact filtering with held-up sediment, the area of the phases’ contact increases, but there is a need for strict observance of the speed of the water flow and an extended contact time (45 min.). Therefore, our tasks were to increase the active contact area of the catalyst pellicle of the iron (III) sediment and to reduce the time ofthe contact between water and the held-upsediment. Deferrisation was carried out in a horizontal absorber bucket of dispersants,in which intensive dispersion significantly increases the area of the phases’ contact in the system. Thus, if the pH of water was 6.4 to 7.8 and the temperature was 291 K,the achieved deferrisation was highly efficient, with low concentration of iron (III) compounds in the volume of the researched water in the process of dispersion—0.02 and 0.05 mol Fe3+/m3. The time of the contact between the purified water and the compounds of the sediment was 15 to 80 sec, depending on the pH of the water and the dose of the applied iron (III) compounds. The obtained results can serve as a basis for the development of a resource and energy saving technology of groundwater deferrising with recirculation of the newly formed sediment.